2020
DOI: 10.21203/rs.3.rs-25554/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative analysis of differentially expressed proteins in psoriasis vulgaris using tandem mass tags and parallel reaction monitoring

Abstract: BackgroundPsoriasis vulgaris (PV) is a chronic autoimmune inflammatory disease with epidermal hyperkeratosis and parakeratosis.MethodsThe study was to elucidate the pathogenesis of PV by quantitative proteomic analysis of skin lesion biopsies of PV and healthy tissues with tandem mass tags (TMTs) coupled with liquid chromatography–mass spectrometry (LC-MS)/MS.ResultsA total of 4562 differentially expressed proteins (DEPs) between PV lesional tissues (n = 11) and healthy tissues (n = 11) were identified, of whi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A similar study showed that the ribosome pathway might be associated with inflammation [ 54 ]. Moreover, results of Li et al's study indicated that selected DEGs in psoriasis were enriched in the ribosomal pathway [ 55 ]. rRNA processing is required for 28S and 5.8S rRNA maturation and proper ribosome biogenesis and plays a role in innate immune signaling [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar study showed that the ribosome pathway might be associated with inflammation [ 54 ]. Moreover, results of Li et al's study indicated that selected DEGs in psoriasis were enriched in the ribosomal pathway [ 55 ]. rRNA processing is required for 28S and 5.8S rRNA maturation and proper ribosome biogenesis and plays a role in innate immune signaling [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%